2011
DOI: 10.1007/s13225-011-0090-4
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic studies of the Penicillium glabrum complex and the description of a new species P. subericola

Abstract: A mycological survey of fungi, present in several stages of the manufacturing of cork discs for champagne stoppers in Portugal, was made. Sixty-nine strains belonging to the Glabra series of the genus Penicillium were isolated and subsequently grouped according to their partial β-tubulin gene sequences. Six groups with different partial β-tubulin gene sequences were observed, and a selection of isolates of each group was made. These selected isolates and various related ex-type strains were subjected to a taxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
(18 reference statements)
4
32
0
Order By: Relevance
“…Nucleotide sequences 1 and 2 in Serbian onion isolates correspond with types 1 and 2 described by Barreto et al. (), while ntseq 3 was unique. Houbraken et al.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Nucleotide sequences 1 and 2 in Serbian onion isolates correspond with types 1 and 2 described by Barreto et al. (), while ntseq 3 was unique. Houbraken et al.…”
Section: Discussionsupporting
confidence: 73%
“…(), and the variability in colony morphology of isolates was seen in cork isolates of P. glabrum as demonstrated by Barreto et al. ().…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Knowledge of the mycobiota that colonizes cork during all the stages of the manufacturing process of cork discs (stoppers) allowed us to locate the phases in which the colonization shifts occur, making it possible to eliminate fungal isolates that could endanger cork. In fact, previous studies (Barreto et al ., ,c) showed that the most common fungal species isolated in post‐boiling cork did not produce any chemical compound that could spoil the final product.…”
Section: Discussionmentioning
confidence: 99%